Observations on mosquitoes in Greenland - Nielsen, Erik Tetens; Nielsen, Hedvig Tetens (Meddelelser om Grønland, 1966)
Observations were made on Aedes nearcticus and Aedes nigripes in Narssarssuaq and in Godhavn. In Narssarssuaq the emergence took place about a month earlier than in Godhavn. The velocity of the pupal development of A. nearticus is higher than in any other mosquito so far examined. Matings take place during the very first days after emergence near the breeding areas. Especially during the first days of adult life the males and some of the females feed on nectar obtained exclusively from Salix. A slow dispersal of the females, presumably by wind, may take place over a distances of 3-4 km. Blood-feeding is inhibited by low temperature and high velocity of wind. The annoyance of the biting is enhanced by the method of slow attack. The swarming activity is independent of illumination but correlated positively with temperatures between 7 and 15°, negatively with wind velocities between O and 2 m/sec. Swarming between 5 and 7° only occurred once, probably as a lowering of the threshold caused by a long period of enforced inactivity. There is only one case, so far unaccountable, of swarming at high wind velocity.